Adherence, self-stigma and discontinuation of pharmacotherapy in patients with anxiety disorders - cross-sectional study - Cinculova, Andrea; Prasko, Jan; Kamaradova, Dana; Ociskova, Marie; Latalova, Klara; Vrbova, Kristyna; Kubinek, Radim; Mainerova, Barbora; Grambal, Ales; Tichackova, Anezka (Neuro endocrinology letters, 2017)
INTRODUCTION: Treatment adherence is one of the main factors affecting the success of treatment and, secondarily, the quality of life and social adaptation of the patients. The aim of this study was to investigate the association between self-stigmatization, treatment adherence and history of discontinuation of drug treatment. METHODS: The cross-sectional study was conducted on 120 (98 completed all the questionnaires) neurotic outpatients treated in the University Hospital Olomouc. The following variables were evaluated: the objective and subjective Clinical Global Impression (CGI) scale, Drug Attitude Inventory (DAI-10) questionnaire measuring adherence, Internalized Stigma of Mental Illness (ISMI) scale measuring self-stigma, and a demographic data questionnaire. RESULTS: Data analysis showed no correlation between self-stigmatization and age, age of onset or length of the post-hospitalization phase. However, there were significant correlations between self-stigmatization and the severity of the disorder (assessed by both objective and subjective CGI), number of previous hospitalizations, total number of psychiatrists visited by the patient, the arbitrary discontinuation of medication in the past, and the dose of an antidepressant. Furthermore, self-stigma was significantly negatively correlated with the current treatment adherence. The rate of adherence was negatively correlated with both objective and subjective CGI only. CONCLUSIONS: Self-stigma significantly affects the current adherence to the treatment of neurotic spectrum disorders.
Keywords: Female; anxiolytika; lidé středního věku; sebepojetí; Quality of Life; Cross-Sectional Studies; průzkumy a dotazníky; kvalita života; mužské pohlaví; Humans; Medication Adherence; Self Concept; dospělí; adherence k farmakoterapii; společenské stigma; průřezové studie; lidé; Middle Aged; Surveys and Questionnaires; Social Stigma; Antidepressive Agents; ženské pohlaví; Anti-Anxiety Agents; Anxiety Disorders; Adult; Male; antidepresiva; úzkostné poruchy